Letter from the Princeton University chemistry department to Max Bredig - Taylor, Hugh S. (Hugh Stott) (1944)
Letter of condolence regarding the death of Georg Bredig (1868-1944) from from Hugh Stott Taylor (1890-1974), on behalf of chemistry department of Princeton University, to Max Albert Bredig (1902-1977). Georg Bredig was given a position at Princeton University which allowed him to immigrate to America. The position was meant more as a formality to obtain a visa. Georg Bredig never was able to work at the university due to illness.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Taylor, Hugh S. (Hugh Stott), 1890-1974; Princeton University